A bird's eye view of Ghana's renewable energy sector environment: A Multi-Criteria Decision-Making approach. (June 2021) - Agyekum, Ephraim Bonah; Amjad, Fahd; Mohsin, Muhammad; Ansah, Michael Nii Sanka
Abstract: This study examines Ghana's renewable energy (RE) sector environment using PESTLE analysis (Political, Economic, Social, Technological, Legal, and Environmental). The Analytical Hierarchical Process (AHP) was employed to rank the various identified factors using inputs from 20 experts in Ghana's RE sector. The consulted experts ranked economic factors as the most critical challenge in the sector. According to them, the cost of capital in Ghana is too high, especially for long-term investments such as RE. The country's abundant RE resources and its geographical location were ranked highest in terms of the opportunities in the RE sector. Highlights: A comprehensive assessment of Ghana's renewable energy sector was conducted. A combination of PESTLE and AHP methodologies were employed for the analysis. Inputs from 20 experts in the renewable energy sector were used for the analysis. Economic factors were identified as the most critical challenge for the sector. Geographical location and renewable resources were identified as the highest opportunities.